The Transcription Factor TCF1 Preserves the Effector Function of Exhausted CD8 T Cells During Chronic Viral Infection - Wang, Yifei; Hu, Jianjun; Li, Yiding; Xiao, Minglu; Wang, Haoqiang; Tian, Qin; Li, Zhirong; Tang, Jianfang; Hu, Li; Tan, Yan; Zhou, Xinyuan; He, Ran; et al. (Frontiers in Immunology, 2019)
The long-term persistence of viral antigens drives virus-specific CD8 T cell exhaustion during chronic viral infection. Yet exhausted, CD8 T cells are still endowed with certain levels of effector function, by which they can keep viral replication in check in chronic infection. However, the regulatory factors involved in regulating the effector function of exhausted CD8 T cell are largely unknown. Using mouse model of chronic LCMV infection, we found that the deletion of transcription factor TCF-1 in LCMV-specific exhausted CD8 T cells led to the profound reduction in cytokine production and degranulation. Conversely, ectopic expression of TCF-1 or using agonist to activate TCF-1 activities promotes the effector function of exhausted CD8 T cells. Mechanistically, TCF-1 fuels the functionalities of exhausted CD8 T cells by promoting the expression of an array of key effector function-associated transcription regulators, including Foxo1, Zeb2, Id3, and Eomes. These results collectively indicate that targeting TCF-1 mediated transcriptional pathway may represent a promising immunotherapy strategy against chronic viral infections by reinvigorating the effector function of exhausted virus-specific CD8 T cells.